Record numbers of common wood pigeon (Columba palumbus casiotis) observed in western Nepal during December 2022 - Dangaura, Hiru Lal; Tiwari, Vikram; Chaudhary, Subam; Dangaura, Krishna Deep; Chaudhary, Anand (Nepalese Journal of Zoology, 2023)
The common wood pigeon is a winter migrant to South Asia. The focus of most research on this species has been on the European/Western Asian subspecies, whereas the subspecies Columba palumbus casiotis found in Central and South Asia, that uses the Central Asian Flyway for migration has received little attention. Knowledge of the migration and distribution of this subspecies in the Central Asian Flyway is through occasional data from structured bird surveys, but most information are anecdotal reports from birdwatchers. Often this species is reported in small numbers but occasionally in their hundreds. In December 2022, the species was observed in their thousands (1150, 6500, and 7500) on three separate dates from two locations in western Nepal. Statistically, these numbers are unprecedented, and raise many questions about their migration patterns and conservation needs in Nepal and the Central Asian Flyway.